Comparison of Healthcare Utilization and Costs Between RA Patients Receiving Biological and Conventional Synthetic DMARDs: A Nationwide Population-Based Cohort Study in Taiwan - Chen, Der-Yuan; Yu, Fun; Tuan, Li-Wen; Tang, Chao-Hsiun (Frontiers in Pharmacology, 2019)
Background. The therapy with biological disease-modifying anti-rheumatic drugs (bDMARDs) has proven to rapidly reduce articular symptoms/signs, decrease morbidities and improve health outcome in patients with rheumatoid arthritis (RA) and be cost-effectiveness in Western countries. However, the difference in healthcare utilization and costs between conventional synthetic DMARDs (csDMARDs) and bDMARDs in the treatment of RA patients in Taiwan remains largely unexplored. Methods. Two cohorts of RA patients and their matched controls were identified from the National Health Insurance Research database (NHIRD). The csDMARD cohort comprised of patients who submitted claims during 1997-2003 for cyclosporine≥50 mg/day with concomitant use of ≥2 csDMARDs for ≥28 days (n=1,569), whilst the bDMARD cohort comprised of patients who had ≥1 claim during 2003-2011 for bDMARD (n=1,530). The per-patient per-year healthcare utilization and costs were estimated by bootstrapping method, with a comparison being undertaken between csDMARD and bDMARD. Results. The incremental number of hospitalization days was reduced from 2.3 days for csDMARD to 0.58 day for bDMARD). When compared to csDMARD-treated patients, the incremental total costs and RA-related medication costs were significantly higher in bDMARD-treated patients (US$9,081 vs. US$2,481; US$8,992 vs. US$1,883). However, the combined incremental healthcare utilization costs and non-RA medication costs were significantly lower in bDMARDs-treated patients compared to csDMARD-treated patients (US$374.7 vs. US$1156.2). Conclusion. Although total costs increased as a result of introducing biologics in RA treatment, biologics have undoubtedly given rise to the benefits of reduced healthcare utilization. The increase in medication costs from biologics was offset by the lower costs of healthcare utilization. Our findings suggest that the medication costs of biologics may be alleviated by an improvement in clinical outcomes.